Pengembangan Model Layanan Reservasi Berbasis Web Stasiun Kereta Api Solo Balapan Dengan Antarmuka Bahasa Sehari-hari - Kurniawan, Bryan Anthony, Hernawan Sulistyanto, S.T., M.T (2016)
Development of web-based reservation service model at the train station Solobalapan with everyday language interface is a system application that makes it easy for the assengers who will make the process of booking train tickets and find information about Solobalapan station online. In a Web-based service system resevasi include any information about the schedule of train travel from the station Solobalapan, booking train tickets, rail passenger data, the cost of train tickets, and other information regarding Solobalapan station. The development of this system using the waterfall method and system design using the design model UML (Unified Modeling Language), and using the programming language PHP using MySQL database.. echniques in data collection using field study consisted of direct observation (observation), interviews and iterature. In this study resulted in the reservation system booking train tickets online using everyday language interface and contains the information about Solobalapan station.